Recent advances in surgical strategies and liver transplantation for hepatoblastoma. (16th November 2022) - Honda, Masaki; Uchida, Koushi; Irie, Tomoaki; Hirukawa, Kazuya; Kadohisa, Masashi; Shimata, Keita; Isono, Kaori; Shimojima, Naoki; Sugawara, Yasuhiko; Hibi, Taizo
Abstract: Hepatoblastoma (HB) is the most common malignant liver tumor in children. Although the development of treatment strategies with advances in chemotherapy has greatly improved the prognosis of HB, surgical resection and liver transplantation still play a vital role in the treatment of HB. In recent years, technological innovations have led to the development of new surgical approaches for HB. In this review, we describe the latest research on the surgical management of HB, including new imaging technologies, minimally invasive approaches, and the application of associating liver partition portal vein ligation for staged hepatectomy. We also discuss the current role of liver transplantation, use of ante‐situm or ex‐situ liver resection with auto‐transplantation, and management of metastatic HB. Abstract : Hepatoblastoma is the most common malignant liver tumor in children. In this review, we describe the latest technologies and techniques for the surgical management of hepatoblastoma, including new imaging technologies, minimally invasive approaches, and the application of associating liver partition portal vein ligation for staged hepatectomy. We also discuss the current role of liver transplantation, liver transplant‐related surgical techniques, and management of metastatic hepatoblastoma.